PENGARUH VOLUME PEMBERIAN KREDIT TERHADAP TINGKAT PENDAPATAN BANK PADA PT.BANK DANAMON - Nita Gartini Gunawan, - (2012)
This research examines the phenomenon of income at PT. Bank Danamon is fluctuating. One of the factors that influence the income level is credit volume. Credit is very important for a bank because of the higher volume of credit it will increase the income of a bank. Bank Danamon is the object of research that has good performance, but the credit volume activities that lead to volatile earnings growth is not stable. This research aims to reveal the influence of the credit volume against the income level of PT. Bank Danamon. The method used in this research is descriptive verification. The research was conducted on the data annual publication of financial statements at PT. Bank Danamon 2003 until 2010, which contains information about credit volume and revenue. To analyze the research data, used a simple linear regression. Based on the results of simple linear regression analysis can be seen that the credit volume has a positive effect on the level of bank earnings. Positive effects showed in case of increase in the credit volume, the bank's income level will rise, and otherwise if the value of credit volume decline, the income level will decline.